Biological control of dryocosmus kuriphilus yasumatsu with the parasitoid torymus sinensis Kamijo - João Cardoso; Maria Teresa Almeida; Albino Bento (Instituto Politécnico de Viseu, 2021)
Introduction: The chestnut gall wasp, Dryocosmus kuriphilus Yasumatsu (Hymenoptera: Cynipidae), is a gall inducing insect original from China that attacks the Castanea genus and can significantly hinder production of chestnut trees. The most effective and used method of control of D. kuriphilus is based on the releases of Torymus sinensis Kamijo (Hymenoptera: Torymidae), a specific parasitoid of D. kuriphilus and native in its natural habitat of origin (China). Objectives: To evaluate T. sinensis ability to establish a population, its dispersion ability and the effect of the release density on the populations of D. kuriphilus in the Portuguese region of Minho. Methods: T. sinensis releases were made in three sites in the Barcelos and Viana do Castelo counties. Results: The presence of T. sinensis was found in three sites of release one year after the releases and in two sites two years after the releases. Presence of T. sinensis was also found at 200 meters distance from the release sites. Conclusion: The average parasitism rates found due to T. sinensis were between 1.3% and 3.9% in the first year, and 0.8% and 13% in the second year, which are within the range described in the international literature.